Treatments for different types of ERCP-related Stapfer IV injury: a case report and literature review - Liang, Hao; Yang, Min; Liu, Yuan-Jun (Frontiers in Medicine, 2025)
BackgroundAs the endoscopic retrograde cholangiopancreatography (ERCP) is commonly used, some rare ERCP-related perforation cases have garnered attention. This study aims to report a rare case of Stapfer IV injury accompanied by severe infections and review the appropriate treatment methods for patients with different types of Stapfer IV injury.Case summaryA female patient received ERCP treatments, but she soon presented with massive diffuse abdominal and thoracic gas accompanied by severe infections. In the following upper gastrointestinal radiography examination, no signs of gastrointestinal perforations were observed. After receiving antibiotic treatments and percutaneous transhepatic gallbladder drainage therapy, the patient recovered and was discharged. Finally, she was diagnosed with Stapfer IV injury and cholecystitis.ConclusionSimple Stapfer IV injury was not a true perforation, and the conservative treatment was feasible. When a severe infection occurs in a patient with Stapfer IV injury, the other complications of ERCP procedures, such as cholecystitis, should be taken into consideration. Interventions for the source of infections, not just for the Stapfer IV injury, might be effective.